ANALISIS MODUL AJAR PADA KURIKULUM MERDEKA BELAJAR DI SD AL-ANSHOR PAGARALAM - Marsa Ella; Muhammad Dhori; Geareta Ananda; Al-Amin (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
This study analyzes the teaching module on the implementation of Merdeka Curriculum at Al-Anshor Pagaralam Elementary School, which aims to determine the function and influence of the teaching module in assisting the flexible and contextual teaching and learning process. the method used is descriptive qualitative, through data collection by interview, observation, and documentation. The results of the study state that the teaching module helps teachers organize learning based on student needs, provides creative learning, and helps improve the profile of Pancasila students. However, obstacles are still faced, such as the lack of teaching guidance and learning facilities. this study discusses the importance of continuous training for teachers when improving effective and relevant teaching modules. the authenticity of local values in teaching modules can be suggested to develop the relevance and meaning of learning. these findings provide important insights for the implementation of Merdeka Curriculum in various educational units.